Electronic Persons ? - Caruana, Louis (Gregorianum, 2020)
To describe computers and sophisticated robots, many people today have no problemusing personal attributes. Alan Turing published his famous intelligence test in 1950. From that time onwards, computers have gained increasingly higher status in thisregard. Computers and robots nowadays are not only intelligent. They perceive, theyremember, they understand, they decide, they play and so on. Recently, another suchstep has occurred but, this time, many researchers are seriously concerned. In February2017, the European Parliament passed a Resolution to attribute legal personhood tointelligent robots. If this is accepted as law, it will have very serious consequencesfor our self-understanding and for the way we live together as a community. TheEU Resolution has stimulated various studies, arising mainly from the area of legalstudies. It is urgent that the response include also a philosophical evaluation regardingthe fundamental concepts at play. This paper seeks to make a contribution preciselyin this area. It explores the attribution of legal personhood to machines by focusingon what is happening at the level of meaning. It explores crucial concepts likeresponsibility, autonomy, person and quasi-person by drawing inspiration from theseminal works of Aristotle and L. Wittgenstein and from the ensuing debates betweencurrent philosophers like P. Hacker and D. Dennett. The results of this paper indicatewhat dangers could lie ahead and what could be the right way to avoid them.